Efficient irrigation management and system turnover (TA 937-INO-Indonesia) Final Report. Vol. 1 - Summary and recommendations - International Irrigation Management Institute (International Irrigation Management Institute, 1989)
Vol. 1 - Summary and recommendations; Vol. 2 - Efficient irrigation management; Vol. 3 - Small scale irrigation turnover program